Loss estimation of a building subjected to earthquake excitions - Lin, Dennis JinZhen (2014)
Natural disasters have always resulted in significant consequences, such as loss of lives and destruction of buildings and infrastructure, whenever it happened. Earthquake is no exception and it seems to be happening more frequent as compared to the past, with even more adverse impact. Some of such recent earthquakes are the 2004 Aceh, Indonesia and the 2011 Tohoku, Japan earthquakes, which resulted in not just a huge amount of lives lost but also triggered tsunamis which led to even more devastating impact, and the two Chile earthquakes from just a few months ago which happened within less than twenty-four hours of each other. Hence making it even more so compelling to be able to estimate the potential losses from such catastrophic events so as to reduce the subsequent potential damages or losses and assist in speeding up the recovery process. Probabilistic loss estimation has been analyzed and used for many years to better predict the occurrence of such an event and estimate the potential losses it will cause. But such methods are not efficient enough due to the large amount of variables involved nor are they able to predict the rarer events that results in catastrophic consequences such as the 2011 Tohoku earthquake. A new method making use of stochastic subset simulation along with Metropolis algorithms is proposed in this paper to better compute such losses more efficiently. Taking into account the uncertainties from the modelling of future ground motion, structural modelling and models for damage and loss analysis, the proposed method will be able to evaluate the seismic loss exceedance probability which can provide the seismic loss distribution probability including the tail part. An illustrative example involving a multi-storey inelastic building will be used in the paper to show the effectiveness and efficiency of the proposed method.